World's first automated volcano forecast predicts Mount Etna's eruptions. (22nd November 2018) - Hall, Shannon
System tracks infrasound waves to determine when an eruption is imminent — and alerts the Italian government. System tracks infrasound waves to determine when an eruption is imminent — and alerts the Italian government.